Samson and the Bees as a Myth An Anthropological Reading - Adar-Bunis, Mattat (2020)
In this article I suggest that the biblical Samson story (Judges 13-16, 18) is a late reconstruction of a pagan myth recounting the life, deeds, and death of Samson the magician. When Samson senses that his death is imminent, he performs a private resurrection ritual for himself, in which bees, accompanied by a lion, play a central role. As in myths from some neighboring cultures, in the Samson myth bees are blessed with the supernatural power to return to life in the spring after dying in the winter and to resurrect the whole of nature. The bees swarming in the cadaver of the lion Samson kills bring the lion back to life in their own form. Samson, who in many ways resembles both a bee and a lion, performs magic based on resemblance to ensure his future return to life.
Keywords: Samson; Bees; Death; Life; Lion; Myth; Resurrection; Ritual; structural analysis; Sympathetic Magic